Reassessing long-term exhumation rates in magmatic terranes - F.J. Cooper; B.A. Adams; S.I.R. Dahlström; T.A. Ehlers; M.C. van Soest; K.V. Hodges; B.R. Jicha; B.S. Singer; J. Cortes Yañez; R.J. Perkins (Earth and Planetary Science Letters, 2026)

Drying Halves Decomposition Rates in River Networks by Decreasing Decomposer Diversity - Rubén del Campo; Thibault Datry; Arnaud Foulquier; Naiara López‐Rojo; Loïc Chalmandrier; Zoltán Csabai; David Cunillera‐Montcusí; Amaia A. Rodeles; Francisco J. Peñas; Bálint Pernecker; Núria Bonada; José Barquín; et al. (Global Change Biology, 2026)
River drying is intensifying worldwide due to climate change and increasing water abstraction, with major consequences for riverine biodiversity and ecosystem functioning. In river networks, drying not only alters local environmental conditions but also disrupts hydrological connectivity, reshaping the movement of organisms and resources at the river network scale. Leaf litter decomposition—a key ecosystem function in freshwater systems—is particularly sensitive to changes in the structure of decomposer communities. We hypothesized that spatiotemporal patterns of drying regulate decomposition by altering the diversity and composition of detritivorous macroinvertebrates, bacteria and fungi. We combined data from six European river networks spanning a wide latitudinal gradient to assess how local drying intensity and regional hydrological connectivity affect decomposition through changes in these decomposer groups. We found that short drying events (≤ 6 dry days) reduced decomposition rates by up to 50% mainly mediated by changes in the composition and diversity of decomposer communities. Drying decreased the diversity of groups contributing to decomposition, shifting the control of this function from a balanced contribution of fungi, bacteria and detritivores in perennial rivers to dominance by dry‐tolerant but less efficient bacteria in drying rivers. These community shifts persisted for months after flow resumption, causing sustained reductions in decomposition also in flowing conditions. Regional hydrological connectivity alleviated these negative effects of local drying by facilitating the recovery of more efficient aquatic decomposers. However, this effect depended on the river network. In more arid networks, stronger fragmentation hindered the recovery of decomposer communities after flow resumption. Overall, our results evidence that spatiotemporal patterns of drying can regulate the linkages between community structure and ecosystem functioning in river networks. As drying events become more frequent and prolonged, shifts in decomposers' diversity are likely to alter carbon cycling and energy fluxes in freshwater ecosystems under global change.

Predictions of New Horizons’ termination shock crossing - Jonathan Gasser; Justyna M. Sokół; Heather A. Elliott; Maher A. Dayeh; Kelsi N. Singer; S. Alan Stern; Igor Baliukin; Sergey Korolkov; Pontus C. Brandt; Joel W. Parker; Andrew R. Poppe; Anne J. Verbiscer; et al. (Advances in Space Research, 2026)

Prediction of Adverse effects of Geomagnetic storms and Energetic Radiation (PAGER) project - Yuri Y. Shprits; Tony Arber; Michael Liemohn; Ondřej Santolík; Keith Bennett; Stefano Bianco; Melanie Burns; Angelica Castillo; Marina García Peñaranda; Bernhard Haas; Julia Himmelsbach; Artem Smirnov; et al. (Advances in Space Research, 2026)

Principal results of the Portoviejo (Ecuador) seismic microzonation project and importance for seismic hazard mitigation - Michael Schmitz; Hugo Yepes; Julio J. Hernández; Luis Yegres; André Singer; Luz M. Rodríguez; Duilio Marcial; Javier Sánchez-Rojas; Kenny García; Víctor Rocabado; Pablo B. Palacios; José M. Marrero; et al. (Natural Hazards, 2025)
The 2016 Mw7.8 Pedernales earthquake caused extensive damage along the central Ecuadorian coastline, resulting in 661 casualties, 4859 injured and the collapse of numerous buildings. The city of Portoviejo (Ecuador), located 140 km from the epicenter, was one of the most severely impacted municipalities with approximately 10% of its buildings damaged and 40 reinforced concrete buildings in the city center collapsed. A seismic microzonation study was conducted in Portoviejo to better understand the damage distribution and guide reconstruction efforts and future engineering projects. Based on a seismic hazard assessment and through equivalent linear analyses of multiple soil profiles integrating geological, geotechnical, and geophysical investigations, the study revealed that local conditions significantly influenced seismic ground motion. Specifically, the low Vs30 values, in the valley generally between 225 and 180 m/s, and even lower in some areas, played a critical role. Additionally, these conditions, associated with fluviomarine sandy deposits, contributed to induced effects such as soil liquefaction, which was a key factor in structural damage and infrastructure failure. These findings were used as primary criteria for delineating seismic microzones in the flat areas of the valley. The technical results of the seismic microzonation study, including response spectra for seismic microzones and soil liquefaction potential assessment, have been incorporated into municipal codes. While landslide hazard in Portoviejo is generally low, the risk could increase under extreme events. This integration has enhanced the city’s understanding of its natural environment and contributed to seismic risk mitigation efforts introducing site-specific parameters in the local building code.

Analysis of host and gut microbial biotransformation products of kratom (Mitragyna speciosa) by mass spectrometry - William J. Crandall; Ken H. Liu; Choon M. Lee; Grant Singer; Jaclyn Weinberg; Edward T. Morgan; Dean P. Jones; Cassandra L. Quave (Phytochemistry Letters, 2025)

Thermally driven ultrapure water production for water electrolysis – A techno-economic analysis of membrane distillation - R. Schwantes; Y. Morales; E. Pomp; J. Singer; K. Chavan; F. Saravia (Desalination, 2025)

The East Palestine train derailment: A complex environmental disaster - Lynn T. Singer; Fredrick Schumacher; James Fabisiak; Laura J. Dietz; Timothy Ciesielski (Neurotoxicology and Teratology, 2025)

The applicability of regional red list assessments for soil invertebrates: first assessment of five native earthworm species in Canada - Helen R. P. Phillips; George G. Brown; Sam W. James; Jérôme Mathieu; John Warren Reynolds; Maheshi E. Dharmasiri; Claire L. Singer; Maria J. I. Briones; Heather C. Proctor; Erin K. Cameron (Biodiversity and Conservation, 2025)
Earthworms (Annelida: Clitellata: Crassiclitellata) are prominent members of the soil community, important to many ecosystem functions. Despite this, and like many other soil invertebrates, they are rarely considered in conservation assessments, including the International Union for Conservation of Nature (IUCN) Red List assessments used to assess species’ extinction risk. To investigate the applicability of the IUCN Regional Red Listing protocol to soil invertebrates, we assessed the conservation status of five earthworm species native to Canada using this protocol and all available occurrence records. In Canada, no earthworm species have yet been assessed by the Committee on the Status of Endangered Wildlife in Canada (COSEWIC). Due to the lack of data on population sizes and their trends, all five species were assessed using their Extent of Occurrence (EOO) (Criterion B). One species was assessed as Vulnerable ( Arctiostrotus vancouverensis) , two were assessed in non-threatened categories ( A. perrieri and Sparganophilus tamesis ), and two were assessed as Data Deficient ( A. fontinalis and Toutellus oregonensis ). For the majority, the main threats identified were the continuing loss of potential habitat due to land conversion and resource exploitation, as well as the effects of climate change. Increasing the amount of data, including but not limited to distribution and habitat preferences, would make the assessment process easier and status decisions better supported. By undertaking regional assessments for five native earthworm species in Canada, we show that Regional Red List assessments are feasible for soil invertebrates.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Large impact features on Ganymede and Callisto as revealed by geological mapping and morphometry - Oliver L. White; Jeffrey M. Moore; Paul M. Schenk; Donald G. Korycansky; Andrew J. Dombard; Martina L. Caussi; Kelsi N. Singer (Icarus, 2025)

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

A critical meta-analysis of predicted no effect concentrations for antimicrobial resistance selection in the environment - Aimee K. Murray; Isobel C. Stanton; Holly J. Tipper; Helen Wilkinson; Wiebke Schmidt; Alwyn Hart; Andrew C. Singer; William H. Gaze (Water Research, 2024)

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

Functional plasticity of HCO3– uptake and CO2 fixation in Cupriavidus necator H16 - Justin Panich; Emili Toppari; Sara Tejedor-Sanz; Bonnie Fong; Eli Dugan; Yan Chen; Christopher J. Petzold; Zhiying Zhao; Yasuo Yoshikuni; David F. Savage; Steven W. Singer (Bioresource Technology, 2024)

Do storm overflows influence AMR in the environment and is this relevant to human health? A UK perspective on a global issue - Holly J. Tipper; Isobel C. Stanton; Rachel A. Payne; Daniel S. Read; Andrew C. Singer (Water Research, 2024)

Respiration and CO2 evasion dynamics in moving streambeds as a response to flow regimes - H. Schulz; Y. Teitelbaum; G.A. Singer; J. Lewandowski; S. Arnon (Journal of Hydrology, 2024)

Characterization of kerogen and bitumen in Type II-S organic-rich chalk as a function of maturity using 2D NMR relaxation - Yunke Liu; Xinglin Wang; George J. Hirasaki; Eva G. Vinegar; Harold J. Vinegar; Philip M. Singer (Fuel, 2024)

Does the Southern Green Anaconda, Eunectes murinus, seek areas of high prey concentration in southeastern Peru? - Patrick S. Champagne; Thomas B. Herman; Paul Rosolie; Dylan Singer; Dan Horton; Carter J. Payne; Lucy Dablin; David Colville; Julio Cardenas; Miryam Quevedo; Trevor Avery; Renata Leite Pitman (Food Webs, 2024)

Melt inclusions in zircon: a window to understanding the structure and evolution of the magmatic system beneath the Laguna del Maule volcanic field - Kei Shimizu; Tyler B. Blum; Chloe E. Bonamici; John H. Fournelle; Christine E. Jilly-Rehak; Noriko T. Kita; Kouki Kitajima; Jacob D. Klug; Will O. Nachlas; Brad S. Singer; Michael J. Spicuzza; Alexander V. Sobolev; et al. (Contributions to Mineralogy and Petrology, 2024)

Unravelling the distribution of three Ammonia species (Foraminifera, Rhizaria) in French Atlantic Coast estuaries using morphological and metabarcoding approaches - Marie P.A. Fouet; Magali Schweizer; David Singer; Julien Richirt; Sophie Quinchard; Frans J. Jorissen (Marine Micropaleontology, 2024)

Unlocking foraminiferal genetic diversity on estuarine mudflats with eDNA metabarcoding - David Singer; Marie P.A. Fouet; Magali Schweizer; Aurélia Mouret; Sophie Quinchard; Frans J. Jorissen (Science of The Total Environment, 2023)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Biodegradation, photolysis, and sorption of antibiotics in aquatic environments: A scoping review - Irene Bueno; Huan He; Amy C. Kinsley; Sarah J. Ziemann; Lauren R. Degn; André J. Nault; Amanda L. Beaudoin; Randall S. Singer; Kristine H. Wammer; William A. Arnold (Science of The Total Environment, 2023)

A framework for evaluating inherent biases within ship design tools - Michael J. Sypniewski; David J. Singer (Ocean Engineering, 2023)

Clinical Nutrition Dashboard for Effective Tracking of Nutrition Metrics - G. Singer; K. Lin; A. Chawla; A. Khan; J. Monclova (Journal of the Academy of Nutrition and Dietetics, 2023)

Evapotranspiration regulates leaf temperature and respiration in dryland vegetation - Christopher L. Kibler; Anna T. Trugman; Dar A. Roberts; Christopher J. Still; Russell L. Scott; Kelly K. Caylor; John C. Stella; Michael Bliss Singer (Agricultural and Forest Meteorology, 2023)

Correction to Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

Equal use of Indigenous and scientific knowledge in species assessments: A case study from the Northwest Territories, Canada - Claire L. Singer; Mélanie R. Routh; Michele J. Grabke; Leon Andrew; Suzanne Carrière; Aimee Guile; Alestine Andre; Allison Thompson; Deborah Simmons; Kaytlin Cooper; Lynda Yonge; Moise Rabesca; et al. (Biological Conservation, 2023)

Migrating Ducks and Submersed Aquatic Vegetation Respond Positively After Invasive Common Carp (Cyprinus carpio) Exclusion from a Freshwater Coastal Marsh - Lauren E. Bortolotti; Robert B. Emery; Paige D. Kowal; Llwellyn M. Armstrong; Vanessa B. Harriman; Howard V. Singer; Michael J. Anteau; Frank B. Baldwin; Cameron Meuckon; Dale A. Wrubleski (Wetlands, 2023)

Long-term response of coastal macrofauna communities to de-eutrophication and sea level rise mediated habitat changes (1980s versus 2018) - Anja Singer; Allert I. Bijleveld; Florian Hahner; Sander J. Holthuijsen; Krischan Hubert; Onur Kerimoglu; Loran Kleine Schaars; Ingrid Kröncke; Karsten A. Lettmann; Timo Rittweg; Gregor Scheiffarth; Henk W. van der Veer; et al. (Frontiers in Marine Science, 2023)
Since the last decades, previous long-term Wadden Sea studies revealed significant changes in the abundance, biomass and spatial distribution of characteristic macrofauna communities in response to environmental changes and anthropogenic stressors. In this study, we performed statistical community analysis for the East-Frisian Wadden Sea (EFWS, southern North Sea) on two reference datasets across a period with severe climatic and environmental changes (1980s-2018). Therefore, historical macrofauna data from the Quantitative Sensitivity Mapping (1980s, SENSI 1) were reanalyzed and compared with data from the Synoptic Intertidal Benthic Survey (SIBES/SENSI 3) collected in 2018. Our results revealed significant quantitative and spatial changes in the characteristic macrofauna communities between the 1980s and 2018, most likely in response to de-eutrophication and sea level rise mediated habitat changes. Since the 1980s, the total number of taxa remained relatively stable (1980s: 90, 2018: 81), but the total abundance decreased by ca. -31% and the total biomass decreased by ca. -45%, particularly in the eastern regions of the study site probably due to de-eutrophication processes. Thereby, the mean abundances/m 2 of ≥ -80% (1980s-2018) in the EFWS of several dominant species decreased: e.g. the gastropod Peringia ulvae , the polychaete Lanice conchilega and the bivalve Mya arenaria . In contrast, the mean abundance/m 2 of one dominant species increased by ≥ +80% (1980s-2018): the invasive bivalve Ensis leei . The mean biomass [g/m 2 ] of three dominant species decreased by ≥ -80% (1980s-2018): P. ulvae , L. conchilega and the amphipod Corophium volutator . In contrast, the mean biomass [g/m 2 ] of one dominant species increased by ≥ +75% (1980s-2018): the polychaete Arenicola marina . In the western part of the EFWS, not only higher abundances of A. marina, but also of L. conchilega and P. ulvae were found in 2018, caused i.a. by sea level rise mediated decreasing mud contents and sand accretion on tidal flats. At the community level, the Oligochaeta/Heteromastus community increased in spatial distribution in the western EFWS in 2018 in the vicinity of increasing mussel/oyster beds.

Separation of solid and liquid components in organic-rich chalks using NMR relaxation - Yunke Liu; Xinglin Wang; George J. Hirasaki; Eva G. Vinegar; Harold J. Vinegar; Philip M. Singer (Fuel, 2023)

Revealing oxidative pentose metabolism in new Pseudomonas putida isolates - Mee‐Rye Park; Rahul Gauttam; Bonnie Fong; Yan Chen; Hyun Gyu Lim; Adam M. Feist; Aindrila Mukhopadhyay; Christopher J. Petzold; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2023)
The Pseudomonas putida group in the Gammaproteobacteria has been intensively studied for bioremediation and plant growth promotion. Members of this group have recently emerged as promising hosts to convert intermediates derived from plant biomass to biofuels and biochemicals. However, most strains of P. putida cannot metabolize pentose sugars derived from hemicellulose. Here, we describe three isolates that provide a broader view of the pentose sugar catabolism in the P. putida group. One of these isolates clusters with the well‐characterized P. alloputida KT2440 (Strain BP6); the second isolate clustered with plant growth‐promoting strain P. putida W619 (Strain M2), while the third isolate represents a new species in the group (Strain BP8). Each of these isolates possessed homologous genes for oxidative xylose catabolism ( xylDXA ) and a potential xylonate transporter. Strain M2 grew on arabinose and had genes for oxidative arabinose catabolism ( araDXA ). A CRISPR interference (CRISPRi) system was developed for strain M2 and identified conditionally essential genes for xylose growth. A glucose dehydrogenase was found to be responsible for initial oxidation of xylose and arabinose in strain M2. These isolates have illuminated inherent diversity in pentose catabolism in the P. putida group and may provide alternative hosts for biomass conversion.

Coupling gas purging with inorganic carbon supply to enhance biohydrogen production with Clostridium thermocellum - Changman Kim; Isaac Wolf; Chang Dou; Lauren Magnusson; Pin-Ching Maness; Katherine J. Chou; Steven Singer; Eric Sundstrom (Chemical Engineering Journal, 2023)

Movement patterns of juvenile green sturgeon (Acipenser medirostris) in the San Francisco Bay Estuary - Michael J. Thomas; Andrew L. Rypel; Gabriel P. Singer; A. Peter Klimley; Matthew D. Pagel; Eric D. Chapman; Nann A. Fangue (Environmental Biology of Fishes, 2022)
Little is known about the distribution and ecology of juvenile green sturgeon throughout their range and specifically within California’s Central Valley and the San Francisco Bay Estuary. The objective of our study was to identify rearing movement patterns of juvenile green sturgeon and their interaction with Delta and Bay habitats. Acoustic biotelemetry was used to record juvenile movements and residence within different regions of this highly modified watershed. We document a diversity of movements exhibited by 31 acoustically tagged juvenile green sturgeon monitored over a 9-month period. The juvenile sturgeon either (1) remained in the Delta or moved (2) into the Carquinez Straits, (3) into San Pablo Bay, (4) into San Pablo Bay but returned to Delta, (5) through the estuary and likely left through the mouth of the bay, (6) or left the estuary only to return later. Spatiotemporal habitat quality varies within and between Delta and Bay habitats. Variation in water year and hydrologic connectivity are likely to influence habitat quality and quantity, and behaviors may be differentially optimized for fitness in response to environmental variation. Our results provide initial evidence supporting multiple behavioral movement patterns and a broad use of regional habitats for green sturgeon in the California Central Valley. This apparent behavioral diversity observed through movement patterns may ensure long-term success of all population segments over time in an extremely variable environment, ultimately supporting overall population stability (i.e., the portfolio effect). Enhanced conservation efforts may be needed to protect juvenile green sturgeon and the habitats they rely upon.

Impact of the temporary closure of a major bridge on local air quality in two large German cities: an accountability study - B. Brach; J. Pikmann; F. Fachinger; P. Kemmerer; B. Büchler; S. Singer; J. König; M. Blettner; F. Drewnick; Emilio A. L. Gianicolo (Air Quality, Atmosphere & Health, 2022)
Despite recent achievements in reducing the contribution of road traffic to air pollution, agreed pollutant standards are exceeded frequently in large parts of Europe. Previous studies assessed the effectiveness of traffic interventions in improving local air quality. However, little research exists on the effect of closures of short road sections over longer periods. The multi-week maintenances on the Theodor Heuss Bridge, the main connection over the river Rhine between the German cities Mainz and Wiesbaden, offered the opportunity to investigate its effect on local air pollution. We measured ambient concentrations of major air pollutants and meteorological parameters at the Theodor Heuss Bridge before, during, and after its closure on 800 m in early 2020. We carried out time-series and closure-dependent evaluations of pollutant concentrations at the bridge accounting for wind direction. Furthermore, we performed regression analyses accounting for wind speed additionally. We compared the results with data from surrounding monitoring stations. We recorded higher concentrations at the Theodor Heuss Bridge compared to outside the closure, especially for particulate matter, nitric oxide, and black carbon. Only with wind from specific directions, we could detect reductions of concentrations during the closure for many pollutants as nitrogen dioxide (− 9.8%; 95% confidence interval: − 10.8– − 8.7%), but not for particulate matter. Since we found similar meteorology-dependent pollution reductions during the closure at both the bridge and the surrounding monitoring stations, we assume that regional meteorological factors overlaid a potential closure-related effect on local air quality. These factors must be accounted for in accountability studies on interventions focusing on short roads.

HIV, pathology and epigenetic age acceleration in different human tissues - Steve Horvath; David T. S. Lin; Michael S. Kobor; Joseph A. Zoller; Jonathan W. Said; Susan Morgello; Elyse Singer; William H. Yong; Beth D. Jamieson; Andrew J. Levine (GeroScience, 2022)
Epigenetic clocks based on patterns of DNA methylation have great importance in understanding aging and disease; however, there are basic questions to be resolved in their application. It remains unknown whether epigenetic age acceleration (EAA) within an individual shows strong correlation between different primary tissue sites, the extent to which tissue pathology and clinical illness correlate with EAA in the target organ, and if EAA variability across tissues differs according to sex. Considering the outsized role of age-related illness in Human Immunodeficiency Virus-1 (HIV), these questions were pursued in a sample enriched for tissue from HIV-infected individuals. We used a custom methylation array to generate DNA methylation data from 661 samples representing 11 human tissues (adipose, blood, bone marrow, heart, kidney, liver, lung, lymph node, muscle, spleen and pituitary gland) from 133 clinically characterized, deceased individuals, including 75 infected with HIV. We developed a multimorbidity index based on the clinical disease history. Epigenetic age was moderately correlated across tissues. Blood had the greatest number and degree of correlation, most notably with spleen and bone marrow. However, blood did not correlate with epigenetic age of liver. EAA in liver was weakly correlated with EAA in kidney, adipose, lung and bone marrow. Clinically, hypertension was associated with EAA in several tissues, consistent with the multiorgan impacts of this illness. HIV infection was associated with positive age acceleration in kidney and spleen. Male sex was associated with increased epigenetic acceleration in several tissues. Preliminary evidence indicates that amyotrophic lateral sclerosis is associated with positive EAA in muscle tissue. Finally, greater multimorbidity was associated with greater EAA across all tissues. Blood alone will often fail to detect EAA in other tissues. While hypertension is associated with increased EAA in several tissues, many pathologies are associated with organ-specific age acceleration.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

The effect of AINTEGUMENTA-LIKE 7 over-expression on seed fatty acid biosynthesis, storage oil accumulation and the transcriptome in Arabidopsis thaliana - Stacy D. Singer; Kethmi N. Jayawardhane; Chen Jiao; Randall J. Weselake; Guanqun Chen (Plant Cell Reports, 2021)

Negative Food Effect of Danirixin: Use of PBPK Modelling to Explore the Effect of Formulation and Meal Type on Clinical PK - Richard S. Lloyd; Martin I. Hingle; Jackie C. Bloomer; Stephen J. Charles; James M. Butler; Alan Paul; Xiaofeng Zhu; Bruce Miller; Donald D’Amico; Alison Donald; Ruth Tal-Singer; Claire Ambery (Pharmaceutical Research, 2020)

Stream microbial communities and ecosystem functioning show complex responses to multiple stressors in wastewater - Francis J. Burdon; Yaohui Bai; Marta Reyes; Manu Tamminen; Philipp Staudacher; Simon Mangold; Heinz Singer; Katja Räsänen; Adriano Joss; Scott D. Tiegs; Jukka Jokela; Rik I. L. Eggen; et al. (Global Change Biology, 2020)
Multiple anthropogenic drivers are changing ecosystems globally, with a disproportionate and intensifying impact on freshwater habitats. A major impact of urbanization are inputs from wastewater treatment plants (WWTPs). Initially designed to reduce eutrophication and improve water quality, WWTPs increasingly release a multitude of micropollutants (MPs; i.e., synthetic chemicals) and microbes (including antibiotic‐resistant bacteria) to receiving environments. This pollution may have pervasive impacts on biodiversity and ecosystem services. Viewed through multiple lenses of macroecological and ecotoxicological theory, we combined field, flume, and laboratory experiments to determine the effects of wastewater (WW) on microbial communities and organic‐matter processing using a standardized decomposition assay. First, we conducted a mensurative experiment sampling 60 locations above and below WWTP discharges in 20 Swiss streams. Microbial respiration and decomposition rates were positively influenced by WW inputs via warming and nutrient enrichment, but with a notable exception: WW decreased the activation energy of decomposition, indicating a “slowing” of this fundamental ecosystem process in response to temperature. Second, next‐generation sequencing indicated that microbial community structure below WWTPs was altered, with significant compositional turnover, reduced richness, and evidence of negative MP influences. Third, a series of flume experiments confirmed that although diluted WW generally has positive influences on microbial‐mediated processes, the negative effects of MPs are “masked” by nutrient enrichment. Finally, transplant experiments suggested that WW‐borne microbes enhance decomposition rates. Taken together, our results affirm the multiple stressor paradigm by showing that different aspects of WW (warming, nutrients, microbes, and MPs) jointly influence ecosystem functioning in complex ways. Increased respiration rates below WWTPs potentially generate ecosystem “disservices” via greater carbon evasion from streams and rivers. However, toxic MP effects may fundamentally alter ecological scaling relationships, indicating the need for a rapprochement between ecotoxicological and macroecological perspectives.

Correction to: Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Correction to: A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

A candidate gene study of intermediate histopathological phenotypes in HIV-associated neurocognitive disorders - Andrew J. Levine; Virawudh Soontornniyomkij; Eliezer Masliah; Janet S. Sinsheimer; Sarah S. Ji; Steve Horvath; Elyse J. Singer; Asha Kallianpur; David J. Moore (Journal of NeuroVirology, 2020)

Seed-specific down-regulation of Arabidopsis CELLULOSE SYNTHASE 1 or 9 reduces seed cellulose content and differentially affects carbon partitioning - Kethmi N. Jayawardhane; Stacy D. Singer; Jocelyn A. Ozga; Syed Masood Rizvi; Randall J. Weselake; Guanqun Chen (Plant Cell Reports, 2020)

Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Historic drought influences outmigration dynamics of juvenile fall and spring-run Chinook Salmon - Gabriel P Singer; Eric D. Chapman; Arnold J. Ammann; A. Peter Klimley; Andrew L. Rypel; Nann A. Fangue (Environmental Biology of Fishes, 2020)

Low river survival of juvenile steelhead in the Sacramento River watershed - Philip Thomas Sandstrom; Arnold J. Ammann; Cyril Michel; Gabriel Singer; Eric D. Chapman; Robert Bruce MacFarlane; Steven T. Lindley; Abbott Peter Klimley (Environmental Biology of Fishes, 2020)

Understanding the chemistry of the artificial electron acceptors PES, PMS, DCPIP and Wurster’s Blue in methanol dehydrogenase assays - Bérénice Jahn; Niko S. W. Jonasson; Hurina Hu; Helena Singer; Arjan Pol; Nathan M. Good; Huub J. M. Op den Camp; N. Cecilia Martinez-Gomez; Lena J. Daumann (JBIC Journal of Biological Inorganic Chemistry, 2020)
Methanol dehydrogenases (MDH) have recently taken the spotlight with the discovery that a large portion of these enzymes in nature utilize lanthanides in their active sites. The kinetic parameters of these enzymes are determined with a spectrophotometric assay first described by Anthony and Zatman 55 years ago. This artificial assay uses alkylated phenazines, such as phenazine ethosulfate (PES) or phenazine methosulfate (PMS), as primary electron acceptors (EAs) and the electron transfer is further coupled to a dye. However, many groups have reported problems concerning the bleaching of the assay mixture in the absence of MDH and the reproducibility of those assays. Hence, the comparison of kinetic data among MDH enzymes of different species is often cumbersome. Using mass spectrometry, UV–Vis and electron paramagnetic resonance (EPR) spectroscopy, we show that the side reactions of the assay mixture are mainly due to the degradation of assay components. Light-induced demethylation (yielding formaldehyde and phenazine in the case of PMS) or oxidation of PES or PMS as well as a reaction with assay components (ammonia, cyanide) can occur. We suggest here a protocol to avoid these side reactions. Further, we describe a modified synthesis protocol for obtaining the alternative electron acceptor, Wurster’s blue (WB), which serves both as EA and dye. The investigation of two lanthanide-dependent methanol dehydrogenases from Methylorubrum extorquens AM1 and Methylacidiphilum fumariolicum SolV with WB, along with handling recommendations, is presented. Graphic abstract Lanthanide-dependent methanol dehydrogenases. Understanding the chemistry of artificial electron acceptors and redox dyes can yield more reproducible results.

Knee extension with blood flow restriction: Impact of cuff pressure on hemodynamics - Tyler J. Singer; Jon Stavres; Steven J. Elmer; Matthew A. Kilgas; Brandon S. Pollock; Sarah G. Kearney; John McDaniel (European Journal of Applied Physiology, 2020)

Castor patatin-like phospholipase A IIIβ facilitates removal of hydroxy fatty acids from phosphatidylcholine in transgenic Arabidopsis seeds - Yingyu Lin; Guanqun Chen; Elzbieta Mietkiewska; Ziliang Song; Kristian Mark P. Caldo; Stacy D. Singer; John Dyer; Mark Smith; Thomas McKeon; Randall J. Weselake (Plant Molecular Biology, 2019)

Sulfur mustard alkylates steroid hormones and impacts hormone function in vitro - Robin Lüling; Helena Singer; Tanja Popp; Harald John; Ingrid Boekhoff; Horst Thiermann; Lena J. Daumann; Konstantin Karaghiosoff; Thomas Gudermann; Dirk Steinritz (Archives of Toxicology, 2019)

Estimation of metapopulation colonization rates from disturbance history and occurrence‐pattern data - H. Fabritius; A. Singer; J. Pennanen; T. Snäll (Ecology, 2019)
Occurrence patterns of many sessile species in dynamic landscapes are not in equilibrium due to their slow rates of metapopulation colonization and extinction. Colonization–extinction data enable the estimation of colonization rates for such species, but collecting the necessary data may require long waiting times between sampling years. Methods for estimating colonization rates of nonequilibrium metapopulations from single occurrence‐pattern data have so far relied on additional data on patch ages and on past patch connectivities. We present an approach where metapopulation colonization rates are estimated from occurrence‐pattern data and from disturbance history data that inform of past patch dynamics and that can be collected together with occurrence‐pattern data. We estimated parameter values regulating patch and metapopulation dynamics by simulating patch network and metapopulation histories that result in present‐like patch network configurations and metapopulation occurrence patterns. We tested our approach using occurrence‐pattern data of the epiphytic lichen Lobaria pulmonaria in Fennoscandian forests, and fire‐scar data that inform of the 400‐yr history of fires and host tree dynamics in the same landscapes. The estimated model parameters were similar to estimates obtained using colonization–extinction data. The projected L. pulmonaria occupancy into the future also agreed with the respective projections that were made using the model estimated from colonization–extinction data. Our approach accelerates the estimation of metapopulation colonization rates for sessile species that are not in metapopulation equilibrium with the current landscape structure.

The European Association for Clinical Pharmacology and Therapeutics—25 years’ young and going strong - Jamie J. Coleman; Caroline Samer; Markus Zeitlinger; Michiel van Agtmael; Gerard A. Rongen; Pierre Marquet; Tabassome Simon; Donald Singer; Vangelis G. Manolopoulos; Ylva Böttiger (European Journal of Clinical Pharmacology, 2019)

Progressive brain atrophy in chronically infected and treated HIV+ individuals - Talia M. Nir; Neda Jahanshad; Christopher R. K. Ching; Ronald A. Cohen; Jaroslaw Harezlak; Giovanni Schifitto; Hei Y. Lam; Xue Hua; Jianhui Zhong; Tong Zhu; Michael J. Taylor; Thomas B. Campbell; et al. (Journal of NeuroVirology, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Created dune slack wetlands effectively host rare early successional turf communities in a dynamic dunefield, New Zealand - Ashley L. Murphy; Nicholas J. D. Singers; Gillian L. Rapson (Journal of Coastal Conservation, 2019)

Limb blood flow and tissue perfusion during exercise with blood flow restriction - Matthew A. Kilgas; John McDaniel; Jon Stavres; Brandon S. Pollock; Tyler J. Singer; Steven J. Elmer (European Journal of Applied Physiology, 2019)

Spatiotemporal occurrence of green sturgeon at dredging and placement sites in the San Francisco estuary - Eric D. Chapman; Emily A. Miller; Gabriel P. Singer; Alex R. Hearn; Michael J. Thomas; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2019)

A randomised controlled trial of the impact of structured written and verbal advice by community pharmacists on improving hypertension education and control in patients with high blood pressure - Ejaz Cheema; Paul Sutcliffe; Martin O. Weickert; Donald R. J. Singer (European Journal of Clinical Pharmacology, 2018)

No reliable gene expression biomarkers of current or impending neurocognitive impairment in peripheral blood monocytes of persons living with HIV - Austin Quach; Steve Horvath; Natasha Nemanim; Dimitrios Vatakis; Mallory D. Witt; Eric N. Miller; Roger Detels; Peter Langfelder; Paul Shapshak; Elyse J. Singer; Andrew J. Levine (Journal of NeuroVirology, 2018)

Climate-Induced Changes in Spring Snowmelt Impact Ecosystem Metabolism and Carbon Fluxes in an Alpine Stream Network - Amber J. Ulseth; Enrico Bertuzzo; Gabriel A. Singer; Jakob Schelker; Tom J. Battin (Ecosystems, 2018)

Effects of social adversity and HIV on subcortical shape and neurocognitive function - April D. Thames; Taylor P. Kuhn; Zanjbeel Mahmood; Robert M. Bilder; Timothy J. Williamson; Elyse J. Singer; Alyssa Arentoft (Brain Imaging and Behavior, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Improvements in brain and behavior following eradication of hepatitis C - Taylor Kuhn; Philip Sayegh; Jacob D. Jones; Jason Smith; Manoj K. Sarma; A. Ragin; Elyse J. Singer; M. Albert Thomas; April D. Thames; Steven A. Castellon; Charles H. Hinkin (Journal of NeuroVirology, 2017)

Expression of ezrin and moesin in primary breast carcinoma and matched lymph node metastases - M. Bartova; J. Hlavaty; Y. Tan; C. Singer; K. Pohlodek; J. Luha; I. Walter (Clinical & Experimental Metastasis, 2017)

Multilevel analysis of neuropathogenesis of neurocognitive impairment in HIV - Andrew J. Levine; Virawudh Soontornniyomkij; Cristian L. Achim; Eliezer Masliah; Benjamin B. Gelman; Janet S. Sinsheimer; Elyse J. Singer; David J. Moore (Journal of NeuroVirology, 2016)

Accelerated epigenetic aging in brain is associated with pre-mortem HIV-associated neurocognitive disorders - Andrew J. Levine; Austin Quach; David J. Moore; Cristian L. Achim; Virawudh Soontornniyomkij; Eliezer Masliah; Elyse J. Singer; Benjamin Gelman; Natasha Nemanim; Steve Horvath (Journal of NeuroVirology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Factors related to HIV-associated neurocognitive impairment differ with age - Gary B. Fogel; Susanna L. Lamers; Andrew J. Levine; Miguel Valdes-Sueiras; Michael S. McGrath; Paul Shapshak; Elyse J. Singer (Journal of NeuroVirology, 2015)

Rare but active taxa contribute to community dynamics of benthic biofilms in glacier‐fed streams - Linda Wilhelm; Katharina Besemer; Christina Fasching; Tim Urich; Gabriel A. Singer; Christopher Quince; Tom J. Battin (Environmental Microbiology, 2014)
Summary Glaciers harbour diverse microorganisms, which upon ice melt can be released downstream. In glacier‐fed streams microorganisms can attach to stones or sediments to form benthic biofilms. We used 454‐pyrosequencing to explore the bulk (16 S rDNA ) and putatively active (16 S rRNA ) microbial communities of stone and sediment biofilms across 26 glacier‐fed streams. We found differences in community composition between bulk and active communities among streams and a stronger congruence between biofilm types. Relative abundances of rRNA and rDNA were positively correlated across different taxa and taxonomic levels, but at lower taxonomic levels, the higher abundance in either the active or the bulk communities became more apparent. Here, environmental variables played a minor role in structuring active communities. However, we found a large number of rare taxa with higher relative abundances in rRNA compared with rDNA . This suggests that rare taxa contribute disproportionately to microbial community dynamics in glacier‐fed streams. Our findings propose that high community turnover, where taxa repeatedly enter and leave the ‘seed bank’, contributes to the maintenance of microbial biodiversity in harsh ecosystems with continuous environmental perturbations, such as glacier‐fed streams.

Predictors of CNS injury as measured by proton magnetic resonance spectroscopy in the setting of chronic HIV infection and CART - J. Harezlak; R. Cohen; A. Gongvatana; M. Taylor; S. Buchthal; G. Schifitto; J. Zhong; E. S. Daar; J. R. Alger; M. Brown; E. J. Singer; T. B. Campbell; et al. (Journal of NeuroVirology, 2014)

Behavior, movements, and habitat use of adult green sturgeon, Acipenser medirostris, in the upper Sacramento River - Michael J. Thomas; Matthew L. Peterson; Eric D. Chapman; Alex R. Hearn; Gabriel P. Singer; Ryan D. Battleson; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Development of low-linolenic acid Brassica oleracea lines through seed mutagenesis and molecular characterization of mutants - Habibur Rahman; Stacy D. Singer; Randall J. Weselake (Theoretical and Applied Genetics, 2013)

A Design Space Verification Protocol for a Small Molecule Drug Substance - Timothy J. N. Watson; Holly Bonsignore; Eileen A. Callaghan-Manning; Stephen T. Colgan; Paul Fitzsimons; Thomas P. Garcia; John G. Groskoph; Michael P. Lynch; Roger Nosal; Megan E. McMahon; Robert A. Singer; Nicholas M. Thomson; et al. (Journal of Pharmaceutical Innovation, 2013)

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

The radiographic anatomy of the normal ovine digit, the metacarpophalangeal and metatarsophalangeal joints - Jennifer S. Duncan; Ellen R. Singer; Jane Devaney; Joanne W. H. Oultram; Anna J. Walby; Bridie R. Lester; Helen J. Williams (Veterinary Research Communications, 2013)

Process, correlation and parameter fitting in species distribution models: a response to Kriticos et al - Stanislaus J. Schymanski; Carsten F. Dormann; Juliano Cabral; Isabelle Chuine; Catherine H. Graham; Florian Hartig; Michael Kearney; Xavier Morin; Christine Römermann; Boris Schröder; Alexander Singer (Journal of Biogeography, 2013)
In a recent article (Dormann et al ., 2012, Journal of Biogeography , 39, 2119–2131), we compared different approaches to species distribution modelling and depicted modelling approaches along an axis from purely ‘correlative’ to ‘forward process‐based’ models. In their correspondence, Kriticos et al . (2013, Journal of Biogeography , doi: 10.1111/j.1365‐2699.2012.02791.x ) challenge this view, claiming that our continuum representation neglects differences among models and does not consider the ability of fitted process‐based models to combine the advantages of both process‐based and correlative modelling approaches. Here we clarify that the continuum view resulted from recognition of the manifold differences between models. We also reinforce the point that the current trend towards combining different modelling approaches may lead not only to the desired combination of the advantages but also to the accumulation of the disadvantages of those approaches. This point has not been made sufficiently clear previously.

Growth, survival, and tag retention of steelhead trout (Oncorhynchus mykiss) and its application to survival estimates - P. T. Sandstrom; A. J. Ammann; C. Michel; G. Singer; E. D. Chapman; S. Lindley; R. B. MacFarlane; A. P. Klimley (Environmental Biology of Fishes, 2013)

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Diel movements of out-migrating Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) smolts in the Sacramento/San Joaquin watershed - Eric D. Chapman; Alex R. Hearn; Cyril J. Michel; Arnold J. Ammann; Steven T. Lindley; Michael J. Thomas; Philip T. Sandstrom; Gabriel P. Singer; Matthew L. Peterson; R. Bruce MacFarlane; A. Peter Klimley (Environmental Biology of Fishes, 2013)

Correlation and process in species distribution models: bridging a dichotomy - Carsten F. Dormann; Stanislaus J. Schymanski; Juliano Cabral; Isabelle Chuine; Catherine Graham; Florian Hartig; Michael Kearney; Xavier Morin; Christine Römermann; Boris Schröder; Alexander Singer (Journal of Biogeography, 2012)
Within the field of species distribution modelling an apparent dichotomy exists between process‐based and correlative approaches, where the processes are explicit in the former and implicit in the latter. However, these intuitive distinctions can become blurred when comparing species distribution modelling approaches in more detail. In this review article, we contrast the extremes of the correlative–process spectrum of species distribution models with respect to core assumptions, model building and selection strategies, validation, uncertainties, common errors and the questions they are most suited to answer. The extremes of such approaches differ clearly in many aspects, such as model building approaches, parameter estimation strategies and transferability. However, they also share strengths and weaknesses. We show that claims of one approach being intrinsically superior to the other are misguided and that they ignore the process–correlation continuum as well as the domains of questions that each approach is addressing. Nonetheless, the application of process‐based approaches to species distribution modelling lags far behind more correlative (process‐implicit) methods and more research is required to explore their potential benefits. Critical issues for the employment of species distribution modelling approaches are given, together with a guideline for appropriate usage. We close with challenges for future development of process‐explicit species distribution models and how they may complement current approaches to study species distributions.

Biotic modifiers, environmental modulation and species distribution models - H. Peter Linder; Olga Bykova; James Dyke; Rampal S. Etienne; Thomas Hickler; Ingolf Kühn; Glenn Marion; Ralf Ohlemüller; Stanislaus J. Schymanski; Alexander Singer (Journal of Biogeography, 2012)
The ability of species to modulate environmental conditions and resources has long been of interest. In the past three decades the impacts of these biotic modifiers have been investigated as ‘ecosystem engineers’, ‘niche constructors’, ‘facilitators’ and ‘keystone species’. This environmental modulation can vary spatially from extremely local to global, temporally from days to geological time, and taxonomically from a few to a very large number of species. Modulation impacts are pervasive and affect, inter alia , the climate, structural environments, disturbance rates, soils and the atmospheric chemical composition. Biotic modifiers may profoundly transform the projected environmental conditions, and consequently have a significant impact on the predicted occurrence of the focal species in species distribution models (SDMs). This applies especially when these models are projected into different geographical regions or into the future or the past, where these biotic modifiers may be absent, or other biotic modifiers may be present. We show that environmental modulation can be represented in SDMs as additional variables. In some instances it is possible to use the species (e.g. biotic modifiers) in order to reflect the modulation. This would apply particularly to cases where the effect is the result of a single or a small number of species (e.g. elephants transforming woodland to grassland). Where numerous species generate an effect (such as tree species making a forest, or grasses facilitating fire) that modulates the abiotic environment, the effect itself might be a better descriptor for the aggregated action of the numerous species. We refer to this ‘effect’ as the modulator. Much of the information required to incorporate environmental modulation effects in SDMs is already available from remote‐sensing data and vegetation models.

Towards novel approaches to modelling biotic interactions in multispecies assemblages at large spatial extents - W. D. Kissling; Carsten F. Dormann; Jürgen Groeneveld; Thomas Hickler; Ingolf Kühn; Greg J. McInerny; José M. Montoya; Christine Römermann; Katja Schiffers; Frank M. Schurr; Alexander Singer; Jens‐Christian Svenning; et al. (Journal of Biogeography, 2012)
Aim Biotic interactions – within guilds or across trophic levels – have widely been ignored in species distribution models (SDMs). This synthesis outlines the development of ‘species interaction distribution models’ (SIDMs), which aim to incorporate multispecies interactions at large spatial extents using interaction matrices. Location Local to global. Methods We review recent approaches for extending classical SDMs to incorporate biotic interactions, and identify some methodological and conceptual limitations. To illustrate possible directions for conceptual advancement we explore three principal ways of modelling multispecies interactions using interaction matrices: simple qualitative linkages between species, quantitative interaction coefficients reflecting interaction strengths, and interactions mediated by interaction currencies. We explain methodological advancements for static interaction data and multispecies time series, and outline methods to reduce complexity when modelling multispecies interactions. Results Classical SDMs ignore biotic interactions and recent SDM extensions only include the unidirectional influence of one or a few species. However, novel methods using error matrices in multivariate regression models allow interactions between multiple species to be modelled explicitly with spatial co‐occurrence data. If time series are available, multivariate versions of population dynamic models can be applied that account for the effects and relative importance of species interactions and environmental drivers. These methods need to be extended by incorporating the non‐stationarity in interaction coefficients across space and time, and are challenged by the limited empirical knowledge on spatio‐temporal variation in the existence and strength of species interactions. Model complexity may be reduced by: (1) using prior ecological knowledge to set a subset of interaction coefficients to zero, (2) modelling guilds and functional groups rather than individual species, and (3) modelling interaction currencies and species’ effect and response traits. Main conclusions There is great potential for developing novel approaches that incorporate multispecies interactions into the projection of species distributions and community structure at large spatial extents. Progress can be made by: (1) developing statistical models with interaction matrices for multispecies co‐occurrence datasets across large‐scale environmental gradients, (2) testing the potential and limitations of methods for complexity reduction, and (3) sampling and monitoring comprehensive spatio‐temporal data on biotic interactions in multispecies communities.

The Minority Training Program in Cancer Control Research: Impact and Outcome Over 12 Years - Rena J. Pasick; Marjorie Kagawa-Singer; Susan L. Stewart; Amy Pradhan; Sherry C. Kidd (Journal of Cancer Education, 2012)

Revisiting the evolution of ecological specialization, with emphasis on insect–plant interactions - M. L. Forister; L. A. Dyer; M. S. Singer; J. O. Stireman; J. T. Lill (Ecology, 2012)
Ecological specialization is a fundamental and well‐studied concept, yet its great reach and complexity limit current understanding in important ways. More than 20 years after the publication of D. J. Futuyma and G. Moreno's oft‐cited, major review of the topic, we synthesize new developments in the evolution of ecological specialization. Using insect–plant interactions as a model, we focus on important developments in four critical areas: genetic architecture, behavior, interaction complexity, and macroevolution. We find that theory based on simple genetic trade‐offs in host use is being replaced by more subtle and complex pictures of genetic architecture, and multitrophic interactions have risen as a necessary framework for understanding specialization. A wealth of phylogenetic data has made possible a more detailed consideration of the macroevolutionary dimension of specialization, revealing (among other things) bidirectionality in transitions between generalist and specialist lineages. Technological advances, including genomic sequencing and analytical techniques at the community level, raise the possibility that the next decade will see research on specialization spanning multiple levels of biological organization in non‐model organisms, from genes to populations to networks of interactions in natural communities. Finally, we offer a set of research questions that we find to be particularly pressing and fruitful for future research on ecological specialization.

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Investigating human audio-visual object perception with a combination of hypothesis-generating and hypothesis-testing fMRI analysis tools - Marcus J. Naumer; Jasper J. F. van den Bosch; Michael Wibral; Axel Kohler; Wolf Singer; Jochen Kaiser; Vincent van de Ven; Lars Muckli (Experimental Brain Research, 2011)

Erratum to: Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giovanni Schifitto; et al. (Journal of NeuroVirology, 2011)

Regional areas and widths of the midsagittal corpus callosum among HIV-infected patients on stable antiretroviral therapies - David F. Tate; Mehul Sampat; Jaroslaw Harezlak; Mark Fiecas; Joseph Hogan; Jeffrey Dewey; Daniel McCaffrey; Daniel Branson; Troy Russell; Jared Conley; Michael Taylor; Giavoni Schifitto; et al. (Journal of NeuroVirology, 2011)

Genetic resistance to diet-induced obesity in chromosome substitution strains of mice - Lindsay C. Burrage; Annie E. Baskin-Hill; David S. Sinasac; Jonathan B. Singer; Colleen M. Croniger; Andrew Kirby; E. J. Kulbokas; Mark J. Daly; Eric S. Lander; Karl W. Broman; Joseph H. Nadeau (Mammalian Genome, 2010)

Stingless Bees: Chemical Differences and Potential Functions in Nannotrigona testaceicornis and Plebeia droryana Males and Workers - Adriana Pianaro; Cristiano Menezes; Warwick Estevam Kerr; Rodrigo B. Singer; Eda Flávia Lotufo R. A. Patricio; Anita J. Marsaioli (Journal of Chemical Ecology, 2009)

Human immunodeficiency virus type 1 in the central nervous system leads to decreased dopamine in different regions of postmortem human brains - Adarsh M Kumar; JB Fernandez; Elyse J Singer; Deborah Commins; Drenna Waldrop-Valverde; Raymond L Ownby; Mahendra Kumar (Journal of NeuroVirology, 2009)

The non-excitable smooth muscle: Calcium signaling and phenotypic switching during vascular disease - Suzanne J. House; Marie Potier; Jonathan Bisaillon; Harold A. Singer; Mohamed Trebak (Pflügers Archiv - European Journal of Physiology, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Characterizing the regulation of the Pu promoter in Acinetobacter baylyi ADP1 - Wei E. Huang; Andrew C. Singer; Andrew J. Spiers; Gail M. Preston; Andrew S. Whiteley (Environmental Microbiology, 2008)
Summary Effective gene trapping and screening requires sensory and regulatory compatibility of both host and exogenous systems. The naturally competent bacterium Acinetobacter baylyi ADP1 is able to efficiently take up and integrate exogenous DNA into the chromosome, making it an attractive host system for a wide range of metagenomic applications. To test the ability of A. baylyi ADP1 to express the XylR‐regulated Pu promoter from Pseudomonas putida mt‐2, we have constructed and examined an A. baylyi ADP1 strain, ADPWH‐ Pu‐lux‐xylR . The Pu promoter in ADPWH‐ Pu‐lux‐xylR was specifically induced by toluene, m ‐, p ‐ and o‐ xylene. The substrate‐induced Pu promoter was highly dependent on the growth medium: it was repressed in rich media until stationary phase, but was immediately induced in minimal medium with glucose as the sole carbon source (MMG). However, the Pu promoter was repressed in MMG when it was supplemented with 5 g l −1 yeast extract. Further investigation showed that the Pu promoter in MMG was repressed by 0.5 g l −1 aspartic acid or asparagine, but not repressed by glutamine. Changing the carbon/nitrogen ratios by addition of ammonia did not significantly affect the Pu promoter activity but addition of nitrate did. These results show that A. baylyi ADP1 reproduced characteristics of the XylR‐regulated Pu promoter observed in its original host. It demonstrates that A. baylyi could provide an excellent genetic host for a wide range of functional metagenomic applications.

The laminin α-1 chain derived peptide, AG73, increases fibronectin levels in breast and melanoma cancer cells - Jean A. Engbring; Rydhwana Hossain; Sherilyn J. VanOsdol; Benjamin Kaplan-Singer; Michael Wu; Suguru Hibino; Jennifer E. Koblinski (Clinical & Experimental Metastasis, 2008)

Cover crop effects on the fate of N following soil application of swine manure - T. B. Parkin; T. C. Kaspar; J. W. Singer (Plant and Soil, 2006)

See globally, spike locally: oscillations in a retinal model encode large visual features - Greg J. Stephens; Sergio Neuenschwander; John S. George; Wolf Singer; Garrett T. Kenyon (Biological Cybernetics, 2006)

Pollination by Sexual Mimicry in Mormolyca ringens: A Floral Chemistry that Remarkably Matches the Pheromones of Virgin Queens of Scaptotrigona sp. - Adriana Flach; Anita J. Marsaioli; Rodrigo B. Singer; Maria Do Carmo E. Amaral; Cristiano Menezes; Warwick Estevam Kerr; Luciane G. Batista-Pereira; Arlene G. Corrêa (Journal of Chemical Ecology, 2006)

Quantitative trait loci for hip dysplasia in a crossbreed canine pedigree - Rory J. Todhunter; Raluca Mateescu; George Lust; Nancy I. Burton-Wurster; Nathan L. Dykes; Stuart P. Bliss; Alma J. Williams; Margaret Vernier-Singer; Elizabeth Corey; Carlos Harjes; Richard L. Quaas; Zhiwu Zhang; et al. (Mammalian Genome, 2005)

Bioaugmentation for bioremediation: the challenge of strain selection - Ian P. Thompson; Christopher J. Van Der Gast; Lena Ciric; Andrew C. Singer (Environmental Microbiology, 2005)
Summary Despite its long‐term use in bioremediation, bioaugmentation of contaminated sites with microbial cells continues to be a source of controversy within environmental microbiology. This largely results from its notoriously unreliable performance record. In this article, we argue that the unpredictable nature of the approach comes from the initial strain selection step. Up until now, this has been dictated by the search for catabolically competent microorganisms, with little or no consideration given to other essential features that are required to be functionally active and persistent in target habitats. We describe how technical advances in molecular biology and analytical chemistry, now enable assessments of the functional diversity and spatial distribution of microbial communities to be made in situ . These advances now enable microbial populations, targeted for exploitation, to be differentiated to the cell level, an advance that is bound to improve microbial selection and exploitation. We argue that this information‐based approach is already proving to be more effective than the traditional ‘black‐box’ approach of strain selection. The future perspectives and opportunities for improving selection of effective microbial strains for bioaugmentation are also discussed.

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

The Chemistry of Pollination in Selected Brazilian Maxillariinae Orchids: Floral Rewards and Fragrance - Adriana Flach; Règine Carole Dondon; Rodrigo B. Singer; Samantha Koehler; Maria do Carmo E. Amaral; Anita J. Marsaioli (Journal of Chemical Ecology, 2004)

Biphasic Dissipation Kinetics for Dislodgeable Foliar Residues in Estimating Postapplication Occupational Exposures to Endosulfan - G. K. Whitmyre; J. H. Ross; C. Lunchick; B. Volger; S. Singer (Archives of Environmental Contamination and Toxicology, 2004)

Late Quaternary pollen records from the Lower Cobb Valley and adjacent areas, North‐West Nelson, New Zealand - J. Shulmeister; W. L. McLea; C. Singer; R. M. McKay; C. Hosie (New Zealand Journal of Botany, 2003)
Ten pollen records from the Cobb Valley and adjacent areas in North‐West Nelson are described. Collectively they provide a vegetation record extending from the Last Glacial Maximum to the present day. During the Last Glacial Maximum the uplands of North‐West Nelson were glaciated. By about 17 000 radiocarbon years BP ice had retreated some distance up the Cobb River valley and a podocarp heath and tussockland vegetation covered non‐glaciated areas. By 14 000 radiocarbon years BP, the valley floor and adjacent lower ridges were occupied by montane podocarp forest dominated by Phyllocladus and Halocarpus. Beech forest expanded into some sites as early as 13 000 yr BP but the modern beech cover was not established until the Holocene. Forest cover has fluctuated in response to disturbance over the Holocene, but the most significant recent change, which is related to clearing for pastoralism in the last two centuries, has had surprisingly little impact on the pollen records.

Impacts of Climate Changes on Elk Population Dynamics in Rocky Mountain National Park, Colorado, U.S.A. - Guiming Wang; N. Thompson Hobbs; Francis J. Singer; Dennis S. Ojima; Bruce C. Lubow (Climatic Change, 2002)

N uptake and N status in ponderosa pine as affected by soil compaction and forest floor removal - Armando G. Gomez; Robert F. Powers; Michael J. Singer; William R. Horwath (Plant and Soil, 2002)

Hemifacial microsomia: progress in understanding the genetic basis of a complex malformation syndrome - D. Kelberman; J. Tyson; D. Chandler; A. McInerney; J. Slee; D. Albert; A. Aymat; M. Botma; M. Calvert; J. Goldblatt; E. Haan; N. Laing; et al. (Human Genetics, 2001)

Inbreeding depression and the maintenance of genetic load in Melitaea cinxia metapopulations - Sari Haikola; Wilhelm Fortelius; Robert B. O'Hara; Mikko Kuussaari; Niklas Wahlberg; Ilik J. Saccheri; Michael C. Singer; Ilkka Hanski (Conservation Genetics, 2001)

Role of Patch Size, Disease, and Movement in Rapid Extinction of Bighorn Sheep - Francis J. Singer; Linda C. Zeigenfuss; Leslie Spicer (Conservation Biology, 2001)
The controversy ( ; ) over rapid extinction in bighorn sheep ( Ovis canadensis ) has focused on population size alone as a correlate to persistence time. We report on the persistence and population performance of 24 translocated populations of bighorn sheep. Persistence in these sheep was strongly correlated with larger patch sizes, greater distance to domestic sheep, higher population growth rates, and migratory movements, as well as to larger population sizes. Persistence was also positively correlated with larger average home‐range size ( p = 0.058, n = 10 translocated populations) and home‐range size of rams ( p = 0.087, n = 8 translocated populations). Greater home‐range size and dispersal rates of bighorn sheep were positively correlated to larger patches. We conclude that patch size and thus habitat carrying capacity, not population size per se, is the primary correlate to both population performance and persistence. Because habitat carrying capacity defines the upper limit to population size, clearly the amount of suitable habitat in a patch is ultimately linked to population size. Larger populations (250+ animals) were more likely to recover rapidly to their pre‐epizootic survey number following an epizootic ( p = 0.019), although the proportion of the population dying in the epizootic also influenced the probability of recovery ( p = 0.001). Expensive management efforts to restore or increase bighorn sheep populations should focus on large habitat patches located ≥23 km from domestic sheep, and less effort should be expended on populations in isolated, small patches of habitat.

Role of Patch Size, Disease, and Movement in Rapid Extinction of Bighorn Sheep - Francis J. Singer; Linda C. Zeigenfuss; Leslie Spicer (Conservation Biology, 2001)

How foraging tactics determine host-plant use by a polyphagous caterpillar - M. Singer; J. Stireman (Oecologia, 2001)

The chemical cell biology of zinc: structure and intracellular fluorescence of a zinc-quinolinesulfonamide complex - M. Sarwar Nasir; Christoph J. Fahrni; David A. Suhy; Kevin J. Kolodsick; Christopher P. Singer; T. V. O'Halloran (JBIC Journal of Biological Inorganic Chemistry, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Multicenter randomized trial of fluconazole versus amphotericin B for treatment of candidemia in non-neutropenic patients - P. Phillips; S. Shafran; G. Garber; C. Rotstein; F. Smaill; I. Fong; I. Salit; M. Miller; K. Williams; J. M. Conly; J. Singer; S. Ioannou (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Regional differences in the compaction of chromatin in human G0/G1 interphase nuclei - H. Yokota; M. J. Singer; G. J. van den Engh; B. J. Trask (Chromosome Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

HIV-gp120 induced cell death in hematopoietic progenitor CD34+ cells - N. K. Banda; J. A. Tomczak; E. J. Shpall; J. Sipple; R. K. Akkina; K. S. Steimer; L. Hami; T. J. Curiel; G. Singer Harrison (Apoptosis, 1997)

The use of bile — esculin agar for the taxonomic classification of the family Enterobacteriaceae - S. C. Edberg; S. Pittman; J. M. Singer (Antonie van Leeuwenhoek, 1977)